Study of Mental Illness in Rat Model of Sodium Azide Induced Oxidative Stress - Muhammad Farhan,; Hira Rafi,; Hamna Rafiq,; Fahad Siddiqui,; Ruba Khan ,; Javeria Anis, (Journal of Pharmacy and Nutrition Sciences, 2019)
Aim: Oxidative stress is known as Reactive oxygen species (ROS) accumulation that is caused by reactive ROS and antioxidants imbalance that could be due to decreased antioxidant levels. Oxidative stress is often related to aging, Oxygen metabolism and redox imbalance in cells and tissues. It is a cellular state in which oxidants levels e.g. superoxide (O-2), hydrogen peroxide (H2O2) or nitric oxide (NO) in biological metabolisms exceed the oxidants scavenging capacity of cells. Oxidative stress in brain leads to depression, anxiety, memory impairment and behavioral deficits associated with them. Method: 24 male albino wistar rats were allocated into test and controls groups administered with sodium azide (5 mg/kg bodyweight) (i.p.) and water (p.o.) respectively for 14 days. Behaviors were monitored weekly after 24 hours of sodium azide administration in light/dark box, elevated plus maze, Open field and Morris water maze. Results: Test animals that were administered with sodium azide significantly decreased entries and time spent in illuminated area of light dark box and elevated plus maze while increased latency and fewer square crossed were observed with decreased learning acquisition and memory retention. Conclusion: All the data collected and results analysis determine oxidative stress could cause mood disorders learning disabilities. Sodium azide induced oxidative stress produce behavioral deficits and memory impairment validated it as a neurotoxin.